If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2a + 1) = 60 Reorder the terms: 4(1 + 2a) = 60 (1 * 4 + 2a * 4) = 60 (4 + 8a) = 60 Solving 4 + 8a = 60 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 8a = 60 + -4 Combine like terms: 4 + -4 = 0 0 + 8a = 60 + -4 8a = 60 + -4 Combine like terms: 60 + -4 = 56 8a = 56 Divide each side by '8'. a = 7 Simplifying a = 7
| 3X+2Y=34 | | 61=4+q | | 7x^2+28x+196=0 | | -5(t-1)+t=5t-9 | | 5x^2+45x+70= | | x*2-6x-4=0 | | X(2x-5)+(3x+4)(6x-1)= | | 3x^2+42x+441=0 | | 73x-15=48+99 | | x+(x*.04)=2.75 | | (x+0.2)(x+3.9)=0 | | 28d+1=28 | | x^2+4x+28=0 | | x+x(.04)=2.75 | | 3(7-2h)=9 | | x^2=y-1 | | -s+3=52+21 | | x^2+34x+2= | | -x^2+565x-8250=0 | | (x-y)(x^2-10xy+y^2)=0 | | b-[x+4a+(x-7)]= | | 9+4+4v-2v+6=11 | | 15.6=2x-1.2 | | 80-2(p+1)=-20+48p | | .006x^3=6572 | | 3-2(2)-5=5(2)-22+3(2) | | 144=4q+4q | | 4x-3=3(-1+x) | | x+6forx=13 | | 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 |